Pain Management in Geriatric Hip Fracture Patients with Ultrasound-Guided Continuous Fascia Iliaca Compartment Block: a Pilot Study - Luckanachanthachote, Chayapa; Pangthipampai, Pawinee; Pangthipampai, Pawinee; Iamaroon, Arissara; Luansritisakul, Choopong; Rungmongkolsab, Piyawadee; Tangwiwat, Suwimon (Thai Journal of Anesthesiology, 2022)
Background: Hip fracture is a painful urgency condition in elderly patients. Femoral nerve block, fascia iliaca compartment block (FICB) and lumbar plexus block have shown the benefits in geriatric hip fracture by reducing pain on movement at 30 minutes. Objectives: To determine an effectiveness of preoperative continuous FICB on static and dynamic pain relief after placement. Secondary objectives include morphine consumption, safety of continuous FICB, opioids-related side effects, ambulatory achievement and incidence of in-hospital and 6-weeks morbidities and mortality. Methods: A prospective observational study included 19 geriatric patients scheduled for hip surgery. An anesthesiologist, experienced on ultrasound-guided nerve blocks, performed ultrasound-guided supra-inguinal continuous FICB technique on within 24 hours hospital admission with 20 ml of 0.25% levobupivacaine in patients reported pain numerical rating scale (NRS ≥ 4). NRS at rest and on movement were compared between pre-block and post-block until postoperative day 2, using Wilcoxon signed rank test. Secondary outcome was reported as descriptive data. Results: A total of 19 patients had markedly dynamic pain relief from median pain score of 10 (IQR 8-10) on pre-block to 3 (IQR 0-5), P<0.001 at 30-minute post-block and continued to provide an effective pain relief until 48 hour (P=0.012) after blockade. We did not observe any major catheter-related problems. Incidence of morbidities and mortality were not different from other trials. Conclusion: Early continuous FICB placement has shown as a safe and effective pain management. It can provide titratable analgesia and prolonged analgesic duration. Continuous FICB may be indicated for elderly patients with acute hip fracture underwent operative delay.